Keputusan Pembelian Lipstik Ditinjau dari Persepsi Konsumen pada Mahasiswi Fakultas Ekonomi Universitas Pelita Harapan Medan - Achmad Irvan Dwi Putra; Octaniani Chiwnita; Sarinah Sarinah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study aims to determine the relationship between consumer perception and purchase decision of Economics Faculty Students of Pelita Harapan University Medan. The hypothesis proposed in this research is there any positive correlation between perception consumer and purchase decision of Economics Faculty Students of Pelita Harapan University Medan, assuming that the higher consumer perception, the higher the purchase decision, and vice versa. The sample of this research is as many as 123 students. This research used purchase decision and consumer perception scale. Product Moment (Pearson Correlation) was used to analyze the correlation between two variables. The results of the data analysis showed that the correlation coefficient was 0,510 with a significance value of 0.000 (p <0.05). It shows that there is a positive correlation between consumer perception and purchase decision. The results of data analysis showed a correlation correlation coefficient of 0.261 (p <0.05) and showed that the contribution of a given perception consumer on purchase decision was 26.1 percent, while the remaining 73.9 percent was affected by other factors not examined. From the results, it can be concluded that the hypothesis stating that there is a significance relationship between consumer perception and purchase decision.